Sclerosing epithelioid fibrosarcoma of the kidney: clinicopathologic and molecular study of a rare neoplasm at a novel location - Ohlmann, Carsten-Henning; Brecht, Ines B.; Junker, Kerstin; Van Der Zee, Jill A.; Nistor, Adriana; Bohle, Rainer M.; Stöckle, Michael; Metzler, Markus; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2015)
Sclerosing epithelioid fibrosarcoma (SEF) is a rare fibrosarcoma variant with specific histomorphology and consistent translocation (EWSR1-CREB3L1/2). To date, 110 cases have been reported; only 15 originated within the abdomen. With only 2 cases reported parallel to our study and one case briefly mentioned in a previous series, primary renal SEF is exceptionally rare but might be underrecognized. We herein describe 2 cases affecting a 23-year-old woman and a 43-year-old man. Tumor size was 22 and 4.2 cm, respectively. Patient 1 developed skeletal and multiple pulmonary metastases. She died of disease 82 months later, despite aggressive multimodality therapy. Patient 2 has no evidence of recurrence or metastasis (8 months after surgery). Histologic examination showed similar appearance with monotonous bland medium-sized epithelioid cells with rounded slightly vesicular nuclei and clear cytoplasm imparting a carcinoma-like appearance set within a highly sclerotic hyaline fibrous stroma. The tumor cells were arranged in nests, single cell cords, trabeculae, or solid sheets with frequent entrapment of renal tubules and glomeruli. Immunohistochemistry showed strong expression of vimentin, bcl2, CD99, and MUC4, whereas cytokeratin and other markers were negative. Fluorescence in situ hybridization showed a translocation involving the EWSR1 gene locus in case 2. Molecular analysis in case 1 was not successful due to poor signal quality. To our knowledge, this is the second report documenting primary renal SEF. Awareness of this entity would help avoid misinterpretation as clear cell carcinoma, sclerosing perivascular epithelioid cell tumor, Xp.11 translocation carcinoma, and other more frequent neoplasms at this site.
EVALuna2:6701